Job Insecurity and its Consequences in the Workplace: A Systematic Review of Empirical Evidence - Adiyatma, Kelpin; Nida Hasanati (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Globalization, automation, and economic crises have intensified job insecurity, making it a critical issue in occupational health. This study presents a systematic review of the literature on job insecurity and its workplace consequences. Using PRISMA and SPIDER frameworks, a Scopus search with the keywords “job insecurity” and “impact” identified 12 relevant journals. The findings indicate that job insecurity leads to mental health problems such as stress, anxiety, depression, and burnout, and negatively affects job performance, productivity, and organizational commitment. These effects are influenced by cultural and industrial contexts, individual traits, and the level of support available. Factors such as locus of control, resilience, social support, and transformational leadership moderate or mediate these impacts. Job insecurity is not merely a labor market concern but a multidimensional challenge requiring proactive, evidence-based strategies to protect employee well-being and maintain organizational resilience in an increasingly uncertain employment landscape.